Policy Analysis of the 2013 Curriculum: Impacts and Challenges for Teachers in the Learning Process at Senior High Schools - Farih Muzaky; Muh. Wasith Achadi (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study examines the impact of Indonesia’s 2013 Curriculum (K-13) on secondary school teachers, focusing on its effects on teaching methods, assessment practices, and classroom management. Using a mixed-methods approach, the research integrates quantitative data from surveys and qualitative insights from interviews to evaluate K-13 implementation. The findings indicate that K-13 has led to significant changes in teaching practices, with many teachers adopting more student-centered and competency-based approaches. However, challenges such as insufficient professional development and resource limitations have hindered effective implementation. Rural teachers, in particular, face greater difficulties due to limited resources. Qualitative data reveal that while the emphasis on authentic assessments and collaborative learning has improved student engagement, it has also introduced complexities that require additional support. Teachers expressed a need for clearer guidelines and more practical training to navigate these new demands effectively.